Do socio-demographic and psychological factors predict dietary pattern? - Julie E Griffiths (2010)
Despite governmental strategies to curb chronic disease, obesity and mental health problems, these continue largely unabated. Yet interventions and health education are expensive and would be more cost effective if targeted at high risk groups. The purpose of the thesis was to establish predictors of healthy and unhealthy dietary patterns and thus identify sections of the population to which more effective interventions can be focused. The 'Western' diet has been characterized by higher consumption of refined cereals, processed and red meats, eggs, desserts and high-fat dairy products while the 'Prudent' diet is distinguished by more fruit, vegetables, whole grains, legumes, fish and poultry. The 'Western' diet has been linked with higher incidence of chronic disease. A food frequency questionnaire of a representative sample of the adult U.K. population was reduced using factor analysis to ten dietary patterns, seven of which were consistent with either the Western or Prudent type diet. These dietary styles were related to demographic variables and found to differ depending on gender, education, age and socio-economic background. The present study is unusual in that it considered the influence of a wide range of factors on dietary choice. Women ate more whole-foods while men ate more processed foods; older people preferred sweet foods; the lesser educated ate more savoury foods; the better educated ate more rice, pasta nuts, fruits and salad; higher socio-economic status was associated with eating more whole foods. In particular it was recommended that nutrition education should be targeted at more extraverted young males with less education, from a lower socio-economic background. A more general message is that one should not consider demographic variables in isolation as there are interactions that make simple generalizations misleading.